Cutaneous herpes simplex infections. Issue 1 (February 1990) - Mindel, A; Carney, O; Williams, P
Abstract : OBJECTIVE: To review the clinical features and natural history of cutaneous herpes simplex infections associated with genital herpes. DESIGN: A retrospective case note study of all patients presenting to James Pringle House with this condition between 1983-1987. SUBJECTS: 123 patients were identified. RESULTS: The commonest sites involved were the buttocks 64/186 (34%), suprapubic area 28/186 (15%) and thigh 14/186 (7.5%). Thirty five of the 123 (28%) patients had more than one anatomical site involved. Genital and extragenital recurrences occurred with similar frequency. DISCUSSION: Extragenital cutaneous herpes simplex is not uncommon. Lesions may occur virtually anywhere on the body. HSV should always be considered in the differential diagnosis of vesiculating skin lesions.